1994
DOI: 10.1128/iai.62.6.2628-2632.1994
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin is a lipid A-binding protein

Abstract: Lactoferrin (LF), a cationic 80-kDa protein present in polymorphonuclear leukocytes and in mucosal secretions, is known to have antibacterial effects on gram-negative bacteria, with a concomitant release of lipopolysaccharides (LPS, endotoxin). In addition, LF is known to decrease LPS-induced cytokine release by monocytes and LPS priming of polymorphonuclear leukocytes. Its mechanism of action is incompletely understood. We have now demonstrated by in vitro-binding studies that LF binds directly to isolated li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(127 citation statements)
references
References 22 publications
8
117
2
Order By: Relevance
“…The transport of haem and haem-derived iron in P. gingivalis involves both high and low a¤nity receptors. The high a¤nity, receptor is thought to be a speci¢c binding protein for the protoporphyrin IX ring [21], while the low a¤nity binding sites are unlikely to be speci¢c receptors [22] and include lipopolysaccharides (LPS) [23]. Here we have shown that apoLf reduced haemin uptake by all three species and caused release of cell-bound haemin, both of which support the possibility that the growth inhibitory e¡ect of Lf is due to depriving cells of haemin.…”
Section: Discussionsupporting
confidence: 65%
“…The transport of haem and haem-derived iron in P. gingivalis involves both high and low a¤nity receptors. The high a¤nity, receptor is thought to be a speci¢c binding protein for the protoporphyrin IX ring [21], while the low a¤nity binding sites are unlikely to be speci¢c receptors [22] and include lipopolysaccharides (LPS) [23]. Here we have shown that apoLf reduced haemin uptake by all three species and caused release of cell-bound haemin, both of which support the possibility that the growth inhibitory e¡ect of Lf is due to depriving cells of haemin.…”
Section: Discussionsupporting
confidence: 65%
“…coliforms), because apo-BLF was also shown to possess bactericidal power against a wide range of microorganisms (Dionysius, Grieve, & Milne, 1993). BLF can damage the outer membrane of Gram-negative bacteria via binding to Lipid A lipopolysaccharides (LPS)which compose their asymmetric lipid bilayer membrane (Appelmelk et al, 1994); release thereof causes structural changes, which include loss of membrane potential and integrity. The antibacterial activity of LF also depends on its concentration or the degree of iron saturation of the molecule, and on its interaction with mineral medium constituents (Payne, Davidson, Oliver, & Christen, 1990).…”
Section: Antimicrobial and Antiviral Propertiesmentioning
confidence: 99%
“…In addition, specific portions of Lf molecules are directly toxic to microbes. Lactoferrin increases bacterial cell membrane permeability and directly damages the outer membrane of Gramnegative bacteria (Ellison et al, 1988;Yamauchi et al, 1993;Appelmelk et al, 1994) by binding to lipopolysaccharide (LPS) and blocking its detrimental effects (Appelmelk et al, 1994).…”
Section: Introductionmentioning
confidence: 99%